Earnings Management and Accounting Reporting Fraud: A Theoretical Comparative Approach - Almahrog, Yousf Ebrahim; Morghem, Laila Touhami (مجلة الدراسات الاقتصادية, 2021)
Abstract The term of earnings management is sometimes used in literature as a synonym for accounting reporting fraud. Thereby, this paper aims to review the existing literature to offer a better clarification to the primary characteristics and differentiation between earnings management and accounting reporting fraud. The results of other previous studies have been reviewed to demonstrate the results of this study using a number of alternatives available resources to the collection of the relevant literature. The findings demonstrate that the activities of manipulating financial information continue to prevail in the business environment worldwide, despite the fact that there are strict laws and regulations to prevent earnings management and fraud behaviour. Therefore, defining the motivation of managers manipulative behaviour can enable academics and regulators to establish a framework to distance between earnings management and fraud and to recognize fraudulent actions through attempting to pursue how managers act to achieve their objectives.